Correlation between non-invasive myocardial work indices and main parameters of systolic and diastolic function: results from the EACVI NORRE study. (13th August 2019) - Manganaro, Roberta; Marchetta, Stella; Dulgheru, Raluca; Sugimoto, Tadafumi; Tsugu, Toshimitsu; Ilardi, Federica; Cicenia, Marianna; Ancion, Arnaud; Postolache, Adriana; Martinez, Christophe; Kacharava, George; Athanassopoulos, George D; et al.
Abstract: Aims: The present study sought to evaluate the correlation between indices of non-invasive myocardial work (MW) and left ventricle (LV) size, traditional and advanced parameters of LV systolic and diastolic function by 2D echocardiography (2DE). Methods and results: A total of 226 (85 men, mean age: 45 ± 13 years) healthy subjects were enrolled at 22 collaborating institutions of the Normal Reference Ranges for Echocardiography (NORRE) study. Global work index (GWI), global constructive work (GCW), global work waste (GWW), and global work efficiency (GWE) were estimated from LV pressure-strain loops using custom software. Peak LV pressure was estimated non-invasively from brachial artery cuff pressure. LV size, parameters of systolic and diastolic function and ventricular-arterial coupling were measured by echocardiography. As advanced indices of myocardial performance, global longitudinal strain (GLS), global circumferential strain (GCS), and global radial strain (GRS) were obtained. On multivariable analysis, GWI was significantly correlated with GLS (standardized beta-coefficient = −0.23, P  < 0.001), ejection fraction (EF) (standardized beta-coefficient = 0.15, P  = 0.02), systolic blood pressure (SBP) (standardized beta-coefficient = 0.56, P  < 0.001) and GRS (standardized beta-coefficient = 0.19, P  = 0.004), while GCW was correlated with GLS (standardized beta-coefficient = −0.55, P  < 0.001), SBP (standardized beta-coefficient = 0.71, P  < 0.001), GRS (standardized beta-coefficient = 0.11, P  = 0.02), and GCS (standardized beta-coefficient = −0.10, P  = 0.01). GWE was directly correlated with EF and inversely correlated with Tei index (standardized beta-coefficient = 0.18, P  = 0.009 and standardized beta-coefficient = −0.20, P  = 0.004, respectively), the opposite occurred for GWW (standardized beta-coefficient =−−0.14, P  = 0.03 and standardized beta-coefficient = 0.17, P  = 0.01, respectively). Conclusion: The non-invasive MW indices show a good correlation with traditional 2DE parameters of myocardial systolic function and myocardial strain.